Inhibitory Test of Bay Leaf (Eugenia polyantha) Extract Against Pseudomonas aeruginosa and Escherichia coli - Haerussana, Ayu Nala El Muna; Dwiastuti, Wulan Putri; Sukowati, Cindi Arwan; Widyastiwi, Widyastiwi (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Bay leaf has traditionally been used by Indonesians as a cooking spice and for disease treatment. Bay leaves contain secondary metabolites that are known to have antibacterial properties. The secondary metabolites produced are influenced by several factors, including the growth area and the extraction solvent. The main causative bacteria in nosocomial infections are Pseudomonas aeruginosa and Escherichia coli. This study aimed to evaluate the antibacterial activity of bay leaf extract against the two gram-negative bacteria. The maceration method and 70% ethanol were used to extract bay leaves. The antibacterial activity was evaluated using the disc diffusion method. The extract exhibits the widest zone of inhibition (11.91±0,84 mm) at 100% of concentration against Pseudomonas aeruginosa. The extract showed antibacterial activity against Pseudomonas aeruginosa but not against Escherichia coli.